2022
DOI: 10.2196/37424
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Using the Digital Support Tool MeeToo: Mixed Methods Study

Abstract: Background Digital peer support is an increasingly used form of mental health support for young people. However, there is a need for more research on the impact of digital peer support and why it has an impact. Objective The aim of this research is to examine young people’s experiences of using a digital peer support tool: MeeToo. After the time of writing, MeeToo has changed their name to Tellmi. MeeToo is an anonymous, fully moderated peer support too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Accessibility NR NR There was limited access to the website due to forgetting on not having time. 50% of adolescents reported they would forget to access the website Efficacy = Yes Efficient = NR Ravaccia et al ( 2022 ) To assess the impact of using MeeToo on young people and reasons for these impacts for general wellbeing 1. Usage NR NR At T1, 50% of youth had just started and 37% had been using MeToo for = > 1 mnth.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accessibility NR NR There was limited access to the website due to forgetting on not having time. 50% of adolescents reported they would forget to access the website Efficacy = Yes Efficient = NR Ravaccia et al ( 2022 ) To assess the impact of using MeeToo on young people and reasons for these impacts for general wellbeing 1. Usage NR NR At T1, 50% of youth had just started and 37% had been using MeToo for = > 1 mnth.…”
Section: Methodsmentioning
confidence: 99%
“…We Intervention participation length ranged from 20 days to 12 weeks (M = 7.60 weeks). The average number of modules per intervention was 6.87 (range: 4-12, n = 22), and the average number of modules intended to be completed per week (Ravaccia et al, 2022;Schueller et al, 2019;Sit et al, 2022;Sun et al, 2022), one via telehealth (i.e., Zoom/videoconferencing software; (Harra & Vargas, 2023), and eight via a combination of delivery methods.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, digital technology provides resources to support and educate those seeking help [ 10 , 11 ], a function that played a particularly important role during the COVID-19 pandemic [ 12 ]. Furthermore, there has been an increasing push to harness digital technology to support mental health, for example, the proliferation of mood-monitoring apps [ 13 ]; web-based support services during crises [ 14 ]; and novel social media platforms designed to cater for mental health, such as those providing a forum for young people to express their feelings and obtain peer support [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of the app has identified that Tellmi helps users find new ways of managing their difficulties and that peer support within the app helps users feel less alone and more connected with those experiencing similar issues [ 19 ]. However, Tellmi’s support for young people experiencing severe distress, including suicidal thoughts, is less developed.…”
Section: Introductionmentioning
confidence: 99%